SEPARATION OF POWERS, CHECKS AND BALANCES AND JUDICIAL EXERCISE OF SELF- RESTRAINT: AN ANALYSIS OF CASE LAW - Magabe T Thabo; Kola O Odeku (Obiter, 2021)
The Constitution of the Republic of South Africa, 1996 creates a system in which there is a separation of the powers exercised by the different branches of the State. It also creates a system of checks and balances. The exercise of a power by one arm of state is checked by another to ensure that there is no abuse of state power. Organs of state ought to respect each other and the powers allocated to them by the Constitution. To this end, no organ of state should encroach upon the domain of the other organs. However, the courts wield enormous power because they are the ultimate guardians and custodians of the Constitution in South Africa. Courts have the power to declare any law or conduct unconstitutional. Where decisions have been taken by other arms of the State on matters falling within their exclusive domain and such decisions violate the Constitution, courts have a duty to intervene in order to make organs of state act within constitutional bounds. However, courts should not be overzealous and should not encroach upon the powers of the other arms of the State when exercising their judicial power and authority. Against this backdrop, this article analyses how the South African courts have cautioned themselves to exercise self-restraint in order not to usurp or encroach upon the powers of the other arms of the State while exercising their judicial authority and power.